2005
DOI: 10.1002/ajim.20210
|View full text |Cite
|
Sign up to set email alerts
|

The global burden of non‐malignant respiratory disease due to occupational airborne exposures

Abstract: Occupational airborne particulates are an important cause of death and disability worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
75
1
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 108 publications
(83 citation statements)
references
References 24 publications
4
75
1
3
Order By: Relevance
“…According to an estimate through workforce data and the Carcinogen Exposure (CAREX) database [130], worldwide in 2000 there were 318,000 deaths from COPD and nearly 3,733 million disability-adjusted life-yrs (DALYs) for COPD due to exposure to occupational airborne particulates. The figures for Europe were 39,300 deaths and 468,000 DALYs.…”
Section: Occupational Exposurementioning
confidence: 99%
“…According to an estimate through workforce data and the Carcinogen Exposure (CAREX) database [130], worldwide in 2000 there were 318,000 deaths from COPD and nearly 3,733 million disability-adjusted life-yrs (DALYs) for COPD due to exposure to occupational airborne particulates. The figures for Europe were 39,300 deaths and 468,000 DALYs.…”
Section: Occupational Exposurementioning
confidence: 99%
“…In addition, asbestos-caused mesothelioma was also included in the 2004 estimates for occupational carcinogens: PAFs were from Driscoll et al (88). Asbestosis, silicosis and pneumoconiosis due to occupational exposures were included in the 2004 estimates for airborne particulates: PAFs were from Driscoll et al (89). Hauri et al (90,91) estimated the burden of contaminated injections in health-care settings for the year 2000.…”
Section: Occupational Exposures and Hazardsmentioning
confidence: 99%
“…and for asthma, and 19% for lung function impairment [29]. Moreover, DRISCOLL et al [30] reported that, in 2000, there were 318,000 deaths worldwide from COPD due to occupational airborne exposure. FRIEDMAN et al [31] described the effects of traffic changes in Atlanta (GA, USA), during the 1996 Summer Olympic Games on childhood asthma events (sample of children aged 1-16 years living in the five central counties of metropolitan Atlanta).…”
Section: Reviewmentioning
confidence: 99%